Yemen Bringing Back Business Project : Risky Business - Impact of Conflict on Private Enterprises - Sofan, Sami A (World Bank, Washington, DC, 2019)
Escalating in March 2015, the conflict spanning across Yemen has resulted in massive casualties, a wave of internally displaced persons, substantial infrastructure damage, and hampered service delivery across both the economy and society. The business climate across Yemen has dramatically deteriorated as a result of the conflict, and businesses throughout the country experienced severe disruptions that for many firms constituted a force majeure situation, hindering their ability to either operate effectively or plan ahead for the future. Addressing these challenges requires substantial effort by the GoY and the international community to support the resilience of the private sector and prevent its further deterioration and losses. The loss of private sector wealth and activity of this magnitude is part and parcel to the food insecurity, poverty, public health issues, and defunct service provision that plagues the war-fatigued population. As such, both in the future post-conflict setting and at present, engaging and revitalizing the Yemeni private sector is a crucial and indispensable step towards the successful reconstruction and recovery of Yemen, and the long-term well-being of the population.